2014
DOI: 10.5005/jp-journals-10024-1589
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Relationship between the Maxillary Sinus Floor and Maxillary Posterior Teeth Roots using Cone Beam Computed Tomography

Abstract: Knowing the anatomical relation between the posterior teeth and the maxillary sinus, help the clinician in preoperative treatment planning of the posterior maxillary teeth and avoid problems that may occur during dental practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
31
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 24 publications
6
31
1
6
Order By: Relevance
“…This finding is agreeing with those of Shokri et al 2014 34 & Ok et al 2014 36 as both studies found that the frequency of maxillary molars roots penetrating the MSF was significantly higher in males while the frequency of maxillary molar roots not reaching MSF was higher in females. The explanation of this finding could be based on the differences between males and females in their growth pattern with longer teeth roots in males than in females which predispose to MSF invagination 34 . However Kilic et al 2010 35 , Pagin et al 41 .…”
Section: While Asthana Et Al 2015 42 and Ok Et Al 2014supporting
confidence: 92%
See 2 more Smart Citations
“…This finding is agreeing with those of Shokri et al 2014 34 & Ok et al 2014 36 as both studies found that the frequency of maxillary molars roots penetrating the MSF was significantly higher in males while the frequency of maxillary molar roots not reaching MSF was higher in females. The explanation of this finding could be based on the differences between males and females in their growth pattern with longer teeth roots in males than in females which predispose to MSF invagination 34 . However Kilic et al 2010 35 , Pagin et al 41 .…”
Section: While Asthana Et Al 2015 42 and Ok Et Al 2014supporting
confidence: 92%
“…While in 2009 Jung et al 18 postulated a classification on CBCT images, this classification was used in the current study and in other previous studies including those of Jung et al 2012 33 , Shokri et al 2014 34 and Fry et al 2016 17 , where all utilized CBCT in the evaluation except for Fry et al 17 who utilized CT images. Jung 2009 18 classification as described in the methodology section is composed of 4 types denoted by numbers 0, 1, 2& 3, where the greater the type number the closer are the roots to MSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In literature, the most common etiological factor for oroantral fistula is the traumatic extractions of posterior molars especially the first molars, followed by extraction of the upper premolars and the second molars. (2)(3)(4) Therefore, oroantral communication (OAC) and subsequent development of an oroantral fistula (OAF) is a common post-extraction complication of the upper posterior teeth or surgical operations within the maxilla. If the patient has a healthy sinus, an OAC less than 4 to 5 mm in diameter will most likely heal spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Complications are associated with creating communication between the maxillary sinus and the oral cavity, possible inflammatory processes which may affect the sinus, such as sinusitis, acute or chronic (12,13,14,15). The relationship between the root apices of the teeth and the inferior sinus allows the dental clinician to assess their own abilities as well as to prepare for potential complications and how to deal with them (16).…”
Section: Discussionmentioning
confidence: 99%